Molecular dynamics simulation on the effect of transition metal binding to the N-terminal fragment of amyloid-β. Issue 17 (22nd November 2019) - Turner, Matthew; Mutter, Shaun T.; Platts, James A.
Abstract: We report molecular dynamics simulations of three possible adducts of Fe(II) to the N -terminal 1–16 fragments of the amyloid-β peptide, along with analogous simulations of Cu(II) and Zn(II) adducts. We find that multiple simulations from different starting points reach pseudo-equilibration within 100–300 ns, leading to over 900 ns of equilibrated trajectory data for each system. The specifics of the coordination modes for Fe(II) have only a weak effect on peptide secondary and tertiary structures, and we therefore compare one of these with analogous models of Cu(II) and Zn(II) complexes. All share broadly similar structural features, with mixture of coil, turn and bend in the N -terminal region and helical structure for residues 11–16. Within this overall pattern, subtle effects due to changes in metal are evident: Fe(II) complexes are more compact and are more likely to occupy bridge and ribbon regions of Ramachandran maps, while Cu(II) coordination leads to greater occupancy of the poly-proline region. Analysis of representative clusters in terms of molecular mechanics energy and atoms-in-molecules properties indicates similarity of four-coordinate Cu and Zn complexes, compared to five-coordinate Fe complex that exhibits lower stability and weaker metal–ligand bonding. Communicated by Ramaswamy H. Sarma